Plan de negocios para la creación de una empresa de mudanzas para el cantón Quevedo, provincia de Los Ríos año 2012 - Hurtado Quintana, Roberto Sixto (2012)
The development of research projects, make extraordinarily daily activities of citizens who choose to start a business, the business plan project called for the creation of a moving company for Quevedo city, province of Los Ríos year 2012. Generally a business plan study serves as background for conducting technical studies, economic and financial engineering to determine the viability of a business. Specifically the study conducted Business Plan capitulation is summarized in the following: Chapter one is part of the introductory phase of the project containing the problem formulation, justification, objectives and assumptions. Chapter two theoretical framework underpinning the research, which shows the same theoretical concepts of several authors as WHITE, Mariotti, SAPAG & SAPAG, ILPES, and various Internet sources, they have been confronted in Chapter XV of discussion of the project. Chapter three contains the methodology of research, sustained sources, techniques, types of research methods, which were the support for market research and technical studies, economic and financial evaluation. Chapter four reveals the result found in field research on the demand and supply of moving service. Chapters five, six and seven contain the technical support, economic and financial evaluation of the project, studies have shown that the performance of the project to the large unmet demand for this service in the canton Quevedo and environment. Chapter eight reports found the conclusions and recommendations are suggested for project effectiveness. Chapter nine shows the discussion of research on the comparison of the concepts of authors (bibliography) with the results found in the field research. Chapter ten contains the bibliographic index and exhibits, such as surveys, photos of the researcher conducting market research to the economically active population of the canton Quevedo. With the above background prior to the investigation, it is concluded that the project "Business Plan for creating a moving company for Quevedo Canton province of Los Ríos, 2012," is feasible because market research shows the absence and unmet removals service in canton Quevedo and the initial investment compared to the financial evaluation of sustained future profitability for the project in question.